Improved open-circuit voltage via Cs2CO3-Doped TiO2 for high-performance and stable perovskite solar cells - Sagar Jain (Organic Electronics, 2019)
Organic-inorganic metal halide perovskites have drawn the interest of scientific community due to their suitable optoelectronic properties and high solar cell efficiency. In this report, we demonstrated, for the first time, the application of Cs2CO3 - doped TiO2 as an efficient electron-transporting layer (ETL) in PSCs. Remarkably, the optimized Cs2CO3-doped TiO2 films exhibited improved wetting properties which assisted the deposition of perovskite films and improved the TiO2/perovskite interface by lowering the work function. With X-ray diffraction studies, better crystalline of the perovskite films could be found in the doped devices. Solar cells prepared with the Cs2CO3-doped TiO2 as ETL resulted in a 19% efficiency performance and improved stability.